2022
DOI: 10.3389/fsurg.2022.821600
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma Subtypes Based on Immunologic and Hallmark Gene Sets in Tumor and Non-tumor Tissues

Abstract: BackgroundNon-tumor tissue has a significant impact on the prognosis of head and neck squamous cell carcinoma (HNSCC). Previous studies for HNSCC have mainly focused on tumor tissue, greatly neglecting the role of non-tumor tissue. This study aimed to identify HNSCC subtypes and prognostic gene sets based on activity changes of immunologic and hallmark gene sets in tumor and adjacent non-tumor tissues to improve patient prognosis.MethodsIn the study, we used gene set variation analysis (GSVA) to estimate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…During the malignant transformation of primary cells, new genetic mutations and molecular phenotypes emerge with each generation of offspring, leading to differences in clinical characteristics, therapeutic response, drug resistance, and prognosis of patients 17 19 . In the research, HNSCC cells in different differentiation phases were divided into four subsets on the basis of cell trajectory analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the malignant transformation of primary cells, new genetic mutations and molecular phenotypes emerge with each generation of offspring, leading to differences in clinical characteristics, therapeutic response, drug resistance, and prognosis of patients 17 19 . In the research, HNSCC cells in different differentiation phases were divided into four subsets on the basis of cell trajectory analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we identified 4 molecular subtypes of HNSCC by cell differentiation trajectory, developed a signature based on differentially expressed prognostic DRGs, and constructed a nomogram integrating the signature and prognostic clinical features for predicting clinical outcomes and response to immunotherapy. During the malignant transformation of primary cells, new genetic mutations and molecular phenotypes emerge with each generation of offspring, leading to differences in clinical characteristics, therapeutic response, drug resistance, and prognosis of patients [17][18][19] . In the research, HNSCC cells in different differentiation phases were divided into four subsets on the basis of cell trajectory analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the obtained prognostic PCDRGs, consensus unsupervised clustering analysis were employed with the K ‐means algorithm using the R package “ConsensusClusterPlus.” 40 Criteria for selecting K values were small intra group differences, large inter group differences, and ensuring a sizable sample size in each group 41 . Survival disparities between different PCD clusters were analyzed using survival analysis and a chi‐squared test.…”
Section: Methodsmentioning
confidence: 99%
“…40 Criteria for selecting K values were small intra group differences, large inter group differences, and ensuring a sizable sample size in each group. 41 Survival disparities between different PCD clusters were analyzed using survival analysis and a chi-squared test. The distribution of different PCD clusters were analyzed using PCA, tSNE, and BLCAAP.…”
Section: Consensus Clustering Analysismentioning
confidence: 99%
“…Moreover, the tumour cells scattered in blood are likely to pass through the blood vessels and fix again in the residual stomach, leading to the recurrence of GC. All these circumstances indicate that immune and molecular changes in nontumour tissues have a great influence in the prognosis of GC patients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%